Supplier relationship‐specific investments and the role of safeguards for supplier innovation sharing - Wagner, Stephan M.; Bode, Christoph (Journal of Operations Management, 2014)
AbstractThe vast majority of the supplier innovation literature has focused on how buying firms can effectively “pull” innovations from their suppliers. Yet, we know remarkably little about the factors that contribute to a supplier voluntarily “pushing” innovations to its customers. The present study addresses this research gap in the context of industrial buyer–supplier relationships and with a specific focus on relationship‐specific investments. Drawing on theory from the relationship‐marketing literature and on transaction cost theory, we devise and test a proposed theoretical model that links the level of a supplier's relationship‐specific investments to its sharing of innovative ideas regarding products and processes with customers. The model also considers the role of contract length, relationship age, and buyer–supplier cooperation as possible safeguards. The empirical results suggest that a supplier's relationship‐specific investments encourage a supplier to suggest ideas of process innovations but to refrain from suggestions about product innovations. The latter effect, however, can be attenuated by appropriate formal and informal safeguards.